Improving mental well-being in psychocardiology—a feasibility trial for a non-blended web application as a brief metacognitive-based intervention in cardiovascular disease patients - Larionov, Katharina; Petrova, Ekaterina; Demirbuga, Nurefsan; Werth, Oliver; Breitner, Michael H.; Gebhardt, Philippa; Caldarone, Flora; Duncker, David; Westhoff-Bleck, Mechthild; Sensenhauser, Anja; Maxrath, Nadine; Marschollek, Michael; et al. (Frontiers in Psychiatry, 2023)
Background: Many patients with cardiovascular disease also show a high comorbidity of mental disorders, especially such as anxiety and depression. This is, in turn, associated with a decrease in the quality of life. Psychocardiological treatment options are currently limited. Hence, there is a need for novel and accessible psychological help. Recently, we demonstrated that a brief face-to-face metacognitive therapy (MCT) based intervention is promising in treating anxiety and depression. Here, we aim to translate the face-to-face approach into digital application and explore the feasibility of this approach. Methods: We translated a validated brief psychocardiological intervention into a novel non-blended web app. The data of eighteen patients suffering from various cardiac conditions but without diagnosed mental illness were analyzed after using the web app over a two-week period in a feasibility trial. The aim was whether a non-blended web app based MCT approach is feasible in the group of cardiovascular patients with cardiovascular disease. Results: Overall, patients were able to use the web app and rated it as satisfactory and beneficial. In addition, there was first indication that using the app improved the cardiac patients' subjectively perceived health and reduced their anxiety. Therefore, the approach seems feasible for a future randomized controlled trial. Conclusions: Applying a metacognitive-based brief intervention via a non-blended web app seems to show good acceptance and feasibility in a small target group of patients with CVD. Future studies should further develop, improve and validate digital psychotherapy approaches, especially in patient groups with a lack of access to standard psychotherapeutic care.